Epidemiological Profile of Tuberculosis in Minas Gerais (REMUNOM, 2025)
This article analyzes tuberculosis (TB) cases in the state of Minas Gerais, aiming to identify epidemiological patterns and trends. TB data were collected from the Transparency Portal of Minas Gerais. The file containing the data was in CSV format and was processed using Excel. After cleaning the dataset, relevant adjustments were made to enable analyses aligned with the study’s focus. The study concentrated on epidemiological records from the years 2020 to 2023. After processing, the data were saved in MS Excel and imported into Power BI, allowing for the creation of graphical analyses. Charts exploring the incidence of cases by gender, age group, education level, and region were developed. The results indicated a significant increase in individuals diagnosed with TB in 2023, with a predominance among male patients, highlighting the need to develop specific strategies targeted at this group. Furthermore, a concentration of cases was observed in rural areas, emphasizing the importance of effective treatment strategies for these regions. Notably, in the analysis of cases among females—unlike the male case analysis—there was a more linear distribution across all age groups, as well as a significant incidence among individuals with higher education levels. It was also found that charts related to age group, adherence to available treatments, education level, and other factors provide crucial insights for the study. These findings underscore the importance of public policies aimed at the prevention and treatment of tuberculosis